An Analysis of The Probative Value of Police Investigators Testimony in Narcotics Criminal Trials - Chairun Nisa Dwi Putri; Benny Sumardiana (Dinasti Research, 2025)
This research aims to analyze the position of the testimony of a police investigator in narcotics criminal prosecutions, as well as finding out how judges assess the objectivity of witness testimony from police investigators. This study uses a normative-empirical approach. Using data obtained from legal regulations, jurisprudence and interviews with judges to provide a more in-depth picture of the position of testimony from police investigators and to see how judges assess testimony from a police investigator in a narcotics crime trial. The results of this study indicate that although witness testimony from a police investigator can be used in a narcotics crime trial, the testimony given by a police investigator as a factual witness has minimal evidentiary value. This is because the interests of the investigator in the case being handled can affect the objectivity of his statement and his statement is free and considered by the judge in accordance with the objectivity and credibility of the witness. The presence of investigators as witnesses in court is generally verbal, especially when the defendant states that the Examination Report (BAP) was made under pressure or coercion. In addition, the testimony of the investigator's witness cannot be the main witness in the trial because the existence of the police investigator's witness does not have a clear legal basis that can regulate the existence of the witness as a legitimate witness. Then, the strength of the testimony from the Polri investigators is weak.